Организация пресечения вторжений в компьютерные сети алгоритмами выявления изменений - Балакин, Сергей Вячеславович (НТУ "ХПІ", 2017)
Рассматривается моделирование системы постановки диагноза путем анализа вероятности достоверности различных наборов состояний в структуре проникновения и комбинированных доказательств симптомов для дерева диагностики, представленного деревом спецификации, чтобы максимально точно определить защищенность системы или организма. Исследование заключается в предоставлении необходимой теоретической базы для использования приведенных концепций и теорий, которые могут комбинироваться с современными наработками для повышения результатов эффективности обнаружения вторжений в компьютерной сети.

The modeling of the diagnostic system is considered. Analyzing the probability of estimating the various sets of states of the structure of the penetration of the combined evidence of symptoms for the diagnostic tree is presented by the specification tree in order to ascertain precisely the security of the system or organism. Main aim of the study is to provide the necessary theoretical basis for using the above concepts and theories that can be combined with current developments to enhance the effectiveness of detecting intrusions in a computer network. Given description shows improved results that can improve diagnosis functions and can be used in real-time computer systems.
Organization of prevention of intrusions in computer networks using algorithms for detecting changes
Keywords: моделирование; диагностика; теория Демпстера-Шефера; алгоритмы изменений; правдоподобность; основное убеждение; Dempster-Shаfer theory; basic belief